Clausewitz his life and work - Stoker, Donald J. (Oxford University Press, 2015)
Carl von Clausewitz's On War, is generally considered the greatest text on military theory ever written. Clausewitz is a touchstone for the field today, and is read by scholars, students, and military personnel around the world. And yet to Clausewitz himself, far more important than achieving recognition for his scholarly and theoretical contributions was achieving glory on the field of battle-winning renown not with his pen but with his sword